Comparison of different green‐extraction techniques and determination of the phytochemical profile and antioxidant activity of Echinacea angustifolia L. extracts. Issue 5 (30th May 2019) - Russo, Daniela; Faraone, Immacolata; Labanca, Fabiana; Sinisgalli, Chiara; Bartolo, Mariantonietta; Andrade, Paula B.; Valentao, Patricia; Milella, Luigi; Lanzotti, Virginia; Grauso, Laura
Abstract: Introduction: Nowadays several plant species, such as Echinacea angustifolia L., can be considered natural important sources for therapeutic applications. Echinacea angustifolia is one of the most known medicinal plants, it shows protective and preventive effects against many chronic diseases, thanks to immunostimulant properties, mostly due to its polysaccharides and antioxidants. However, the optimisation of green extraction techniques to respect the environment is, currently, a hard challenge for the recovery of secondary metabolites. Methodology: Hydro‐enzymatic extraction has been performed for the first time, it was compared with other different extraction techniques, for their efficacy in bioactive compound recovery. Phytochemical characterisation has been carried out through high‐performance liquid chromatography diode array detector (HPLC‐DAD) analysis and the antioxidant activity has been also measured. Results: The highest extractive yields and the strongest antioxidant activity was obtained by cellulase and xylanase enzyme extraction. The enzymatic extraction with pectinase enzyme led to a higher polysaccharide content in comparison with the literature. The hydro‐enzymatic extraction method and analytical conditions allowed the identification and quantification of two compounds, to the best of our knowledge, for the first time in E. angustifolia root extract. Conclusion: The optimised extraction methods discussed in this work led to a higher polysaccharides content, in comparison to previous literature results. The enzymatic extraction seems to be the best extraction technique, in terms of antioxidant yield and efficacy in bioactive compound recovery. Abstract : Echinacea angustifolia L. shows beneficial effects against many diseases, thanks to polysaccharide and phenolic compounds. Hydro‐enzymatic extraction, performed here for the first time, was compared with other different extraction techniques. Phytochemical characterisation has been carried out through high‐performance liquid chromatography diode array detector (HPLC‐DAD) analysis, allowing the identification of two compounds for the first time in this species. The optimised extraction methods led to a higher polysaccharides content in comparison to previous literature results. The green enzymatic extraction technique presented the highest yields of antioxidants.